Cognitive Processes and Legal Capacity in Patients With Bipolar Disorder: A Brief Research Report - Saffi, Fabiana; Rocca, Cristiana C. A.; Toschi-Dias, Edgar; Durães, Ricardo S. S.; Serafim, Antonio P. (Frontiers in Psychology, 2022)
The current study verified the association between cognitive process such as attention, executive functioning, and legal capacity in patients with bipolar disorder (BD). The sample consisted of 72 participants, assorted to episodic patients (n = 21), euthymic patients (n = 22), and healthy controls (HCs) (n = 29). We used the following neuropsychological measures: subtests of the Wechsler Abbreviated Intelligence Scale (WASI): vocabulary and matrix reasoning; Continuous Performance Test (CPT); Five Digit Test (FDT); and Rey–Osterrieth Complex Figure (ROCF). Euthymic patients expressed slower processing speed (FDT) compared to HC. They tended to make more errors with slightly worse discrimination, suggesting more impulsiveness (CPT, p < 0.01). On the contrary, episodic patients showed worse discrimination, committed more omissions, were more inconsistent with regard to response speed (CPT-3, p < 0.01), showed more difficulties in organizing their actions (ROCF: copy, p = 0.03), and were more rigid (FDT: flexibility, p = 0.03). The results suggest that bipolar patients in episode express more cognitive impairments that can compromise the quality of legal capacity. These results highlight the need for more protective support for episodic BD patients regarding legal capacity.